Identification of Neuropeptide Y receptors in human articular cartilage: influence of gender and osteoarthritis - Ferreira, Inês Sofia dos Santos Rodrigues (2017)
Dissertação de Mestrado em Farmacologia Aplicada apresentada à Faculdade de Farmácia